2013
DOI: 10.1016/j.pep.2013.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Expression and purification of functional human glycogen synthase-1 (hGYS1) in insect cells

Abstract: SUMMARY We have successfully expressed and purified active human glycogen synthase-1 (hGYS1). Successful production of the recombinant hGYS1 protein was achieved by co-expression of hGYS1 and rabbit glycogenin (rGYG1) using the MultiBac baculovirus expression system (BEVS). Functional measurements of activity ratios of hGYS1 in the absence and presence of glucose-6-phosphate and treatment with phosphatase indicate that the expressed protein is heavily phosphorylated. We used mass spectrometry to further charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 27 publications
5
19
1
Order By: Relevance
“…In addition, a number of non-conventional sites were identified (T54, T372, S412, S486, S652 and S727), albeit at relatively low abundance. Several of these sites have been identified by a recent study where human GYS1 was overexpressed in insect cells [9] and also in global MS screens [20–22] . It might be of interest to perform mutagenesis analysis and examine the impact of these phosphorylation sites on the regulation of GYS1 activity and possibly cellular localisation, as the physiological significance of these non-conventional sites is unknown.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, a number of non-conventional sites were identified (T54, T372, S412, S486, S652 and S727), albeit at relatively low abundance. Several of these sites have been identified by a recent study where human GYS1 was overexpressed in insect cells [9] and also in global MS screens [20–22] . It might be of interest to perform mutagenesis analysis and examine the impact of these phosphorylation sites on the regulation of GYS1 activity and possibly cellular localisation, as the physiological significance of these non-conventional sites is unknown.…”
Section: Resultsmentioning
confidence: 97%
“…Subsequent studies have demonstrated that glycogenin interacts with glycogen synthase and enhances soluble overexpression of glycogen synthase (when ectopically co-expressed with glycogen synthase in cultured cell lines) [4,8] . This has led Khanna et al [9] to make an attempt to co-express GYS1 and glycogenin using MultiBac system in insect cells, which resulted in a successful soluble expression and purification of large quantities of human GYS1 proteins. Direct interaction of the C-terminus of GN with glycogen synthase was first reported by Skurat et al [10] based on a yeast two-hybrid study followed by cellular overexpression experiments and more recently by an X-ray crystal structure of glycogen synthase in complex with a C-terminal 34-residue fragment of GN [11] .…”
Section: Introductionmentioning
confidence: 99%
“…The low activity ratio seen in the WT equine GS enzyme (0.02) is similar to that detectable in baculovirus-generated human GS [48]. Despite both the equine WT and mutant insect-derived enzymes’ phosphorylation (at site 3a) (Figure 5A), the mutant equine enzyme had a high activity ratio, similar to that of the S7A mutant human GS, (which cannot be phosphorylated) (Figure 5B).…”
Section: Resultsmentioning
confidence: 60%
“…Further, the R309H enzyme had significantly lower K m for UDPG even in the absence of G6P and the V max /K m value for the mutant enzyme in the absence of G6P was increased over 60 fold, when compared to the WT enzyme. In contrast, the activity ratio of the WT equine enzyme was similar to that of human GS purified in a similar manner [48]. Further, there was no detectable difference in the extent of 3a phosphorylation between the WT and mutant recombinant enzymes, but despite this, the equine recombinant enzyme behaved similarly to that of a mutant human enzyme that cannot be phosphorylated, both with and without pre-treatment with protein phosphatase 1.…”
Section: Discussionmentioning
confidence: 93%
“…Recombinant human GYS1 glycogen synthase was produced in insect cells and purified as described by Khanna et al [32]. Hexokinase (#1012765501) and pyrophosphatase (#91078329) were from Roche.…”
Section: Methodsmentioning
confidence: 99%